(untitled) (Andamios, Revista de Investigación Social, 2010)
This paper draws on Pedro Henriquez Ureña’s teachings to present some reflections regarding the philosophical practices used in nineteencentury Latin America. These practices were transmitted by means of orality and gestuality and therefore, they can’t be studied merely by accessing the authors’ publications. In the paper we suggest some alternatives on how to study the practices of the transmission of philosophical knowledge. This issue is related to the emotional dimension of Latin-American philosophy, the relationship between rhetoric and philosophy and the existence of philosophical “styles” or “ways of doing” philosophy.